Partai Politik: Tinjauan Strategi Dalam Meraih Dukungan Massa - Syahrul Ibad; Musdalifah Musdalifah (Universitas Muhammadiyah Gorontalo, 2019)
This study discusses political parties reviewing strategies in gaining mass support, the strategy carried out by political parties is to achieve predetermined goals which in this case are referred to as the vision and mission of political parties using techniques, tricks, methods and implementation of tasks by utilizing party structure, so that the work program is in accordance with the wishes of the community. Meanwhile, to uncover the strategy of political parties in gaining mass support, a library research method or approach is used. Literature study or literature can be interpreted as a series of activities related to library data collection methods, reading and recording and processing research materials. Research results show that strategy of political parties in gaining the support of the masses is always trying to fix the party from the party's internal and external parties, so that the party can provide a better change for the community through political party programs and through power struggles in general elections.Penelitian ini membahas tentang partai politik tinjauan strategi dalam meraih dukungan massa, strategi yang dilakukan partai politik ialah untuk mencapai tujuan yang sudah ditentukan sebelumnya yang dalam hal ini disebut sebagai dengan visi dan misi partai politik dengan menggunakan teknik, trik, cara maupun pelaksanaan tugas dengan memamfaatkan struktur partai, sehingga program kerja sesuai dengan keinginan masyarakat. Sedangkan untuk mengungkap strategi partai politik dalam meraih dukungan massa digunakan metode atau pendekatan kepustakaan, Studi pustaka atau kepustakaan dapat diartikan sebagai serangkaian kegiatan yang berkenaan dengan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitian. Hasil Penelitian menunjukkan bahwa strategi partai politik dalam meraih dukungan massa adalah selalu berusaha membenahi partai dari internal partai maupun ekternal partai, sehingga partai bisa memberikan perubahan yang lebih baik bagi masyarakat melalui program partai politik maupun melalui perebutan kekuasaan dalam pemilihan umum.